EV Charging Infrastructure and V2G Concept - Guliyev, Sabir (ADA University, 2023)
The increasing concern over climate change requires the widespread deployment of electric vehicles (EVs). The adoption of electric vehicles involves the establishment of a charging infrastructure. This thesis presents a review of the current EV situation in world, including infrastructure, standards, and the effects of EVCS to the grid. Examining the situation in Azerbaijan, the research investigates the country's ambitious efforts to create a electric vehicle production facility. It assesses the current status of EVs in Azerbaijan, taking into account significant Government initiatives and private companies initiatives like Azpetrol, Elcar.az, Charge.az and the rise of local manufacturers and resellers of fast chargers. This study also conducted an in-depth analysis of pricing of charging of EVs in Azerbaijan. Using a Tesla Model S battery with a capacity of 75 kWh as a reference, I computed the cost of charging and charging time of electric vehicles with this type of battery using several charging options, ranging from a 120 kW level 3 fast charger to a 3.5 kW level 1 charger. The next part analyzes the complex incorporation of EV into the power grid, delving into sophisticated concepts such as EV aggregators, Virtual Power Plants (VPPs), and the architectural details of EVs outfitted with vehicle-to-grid (V2G) systems. This research reveals the potential for significant changes, offering valuable understanding of the changing energy environment and the interactive connection between EVs and the electrical grid. This study also analyzed the prospective effects of EVs on the power grid, and evaluated both the positive and negative consequences. The research offers a comprehensive approach to predict the import of EVs and Hybrid Electric Vehicles (HEVs) into Azerbaijan. This is done by analyzing historical data and use linear regression models to estimate trends from 2019 to 2030. The exploration concludes with analysis of MATLAB Simulink simulations, providing realistic results from situations, such as Grid-to-vehicle (G2V), Vehicle-to-grid (V2G), and a combined G2V-V2G system. This simulation examines the relationship between voltage and current in a single-phase electric vehicle charging system. It analyzes the state of charge (SOC), voltage, and current of the EV battery. These simulations increase understanding of the practical effects of integrating EVs with the power system. To sum up this thesis offers a complete and detailed explanation of the dynamic interaction between Electric Vehicles and the power grid. It includes a thorough examination of worldwide trends and localized initiatives primarily in Azerbaijan.
Keywords: Electric vehicles--Azerbaijan--Infrastructure; Electric vehicles--Azerbaijan--Government policy; Electric vehicles--Azerbaijan--Charging stations; Azerbaijan--Electric vehicles--Economic aspects; Azerbaijan--Power grid--Impact of electric vehicles; IT and Engineering